The Impact of Digital Transformation on Improving the Quality of Public Services: A Case Study at the Palembang City Population and Civil Registration Office - M. Ivan Hidayat; Isabella; Doris Febriyanti (Universitas Muhammadiyah Palu, 2025)
The government's need to improve efficiency, transparency, and quality of public services through the use of digital technology. Digital transformation at the Palembang City Population and Civil Registration Office is one of the tangible forms of E-Government implementation, especially through the implementation of Digital Population Identity (IKD) and population administration information system (SIAK). This change is driven by national regulations and the need to realize fast, accountable, and inclusive services amid the challenges of low digital literacy and human resource readiness. This transformation is important to overcome the constraints of previous manual services and encourage a government system that is more adaptive to the digital era. This research aims to determine the digital transformation of the Palembang City Population and Civil Registration Office in 2024. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observations and documentation at the Palembang City Population and Civil Registration Office. Data analysis is carried out through data collection, data presentation, and verification and confirmation of conclusions. The location of this research is the Palembang City Population and Civil Registration Office located on Jalan Demang Lebar Daun, No.4225, Lorok Pakjo, Kec. The interview resource persons amounted to 9 people, including 1 head of office, 3 employees of the Disdukcapil, 5 communities. The results of this study show that the Digital Transformation of the Palembang City Population and Civil Registration Office in 2024 shows significant achievements in improving the quality of public service governance. The implementation of the population administration information system (SIAK) and Digital Population Identity (IKD) contributes to increasing the efficiency, transparency, and accessibility of services to the community. This success is supported by the availability of adequate technological infrastructure, adaptive regulations, and strategic initiatives such as the